2016
DOI: 10.1002/14651858.cd004730.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and oral agents for managing cystic fibrosis-related diabetes

Abstract: This review has not found any significant conclusive evidence that long-acting insulins, short-acting insulins or oral hypoglycemic agents have a distinct advantage over one another in controlling hyperglycemia or clinical outcomes associated with cystic fibrosis-related diabetes. While some cystic fibrosis centers use oral medications to help control diabetes, the Cystic Fibrosis Foundation (USA) clinical practice guidelines support the use of insulin therapy and this remains the most widely-used treatment me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 40 publications
0
21
0
4
Order By: Relevance
“…Oral diabetes agents are currently not recommended in CFRD. A Cochrane review did not identify any randomized controlled trials other than the CFRDT Trial, where the insulin secretagogue repaglinide was not able to produce sustained weight gain in individuals with CFRD without fasting hyperglycemia . Results of a recently published multicenter European study comparing insulin and repaglinide showed no differences in HbA1c, body mass index (BMI), lung function, or adverse events between the two treatments after 2 years of therapy; they suggest that repaglinide could be considered for treatment of early CFRD .…”
Section: Treatment Of Cfrdmentioning
confidence: 99%
“…Oral diabetes agents are currently not recommended in CFRD. A Cochrane review did not identify any randomized controlled trials other than the CFRDT Trial, where the insulin secretagogue repaglinide was not able to produce sustained weight gain in individuals with CFRD without fasting hyperglycemia . Results of a recently published multicenter European study comparing insulin and repaglinide showed no differences in HbA1c, body mass index (BMI), lung function, or adverse events between the two treatments after 2 years of therapy; they suggest that repaglinide could be considered for treatment of early CFRD .…”
Section: Treatment Of Cfrdmentioning
confidence: 99%
“…Guidelines recommend insulin as first line treatment [2]. Nevertheless there are many centers which use oral antidiabetic drugs for treatment of CFRD [3]. The reasons for this off label use might be the hope to reduce the treatment burden which is even without CFRD very high in CF [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore a direct comparison of the effect of repaglinide versus insulin on BMI, HbA1c and FEV1%pred was not presented. The actual Cochrane report [3] regarding “Insulin and oral agents for managing cystic fibrosis-related diabetes” stated that further studies are needed to establish whether there is clear benefit for hypoglycemic agents. We expect that the results of our study will help to address this clinical need.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations